2020
DOI: 10.1016/j.ijfoodmicro.2020.108887
|View full text |Cite
|
Sign up to set email alerts
|

Water UV-C treatment alone or in combination with peracetic acid: A technology to maintain safety and quality of strawberries

Abstract: Disinfection of fruits is one of the most important steps since they are going to be eaten fresh-or minimally-processed. This step affects quality, safety, and shelf-life of the product. Despite being a common sanitizer in the fruit industry, chlorine may react with organic matter leading to the formation of toxic by-products. Alternative sustainable disinfection strategies to chlorine are under study to minimize environmental and human health impact. Water-assisted UV-C light (WUV-C) is proposed here as an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
(38 reference statements)
4
13
0
Order By: Relevance
“…Values of TPC and TAC of strawberries used for the treatments are in accordance for those already reported in strawberries from the same origin [19,41]. In the present study, TAC and TPC values did not overcome major changes after heat treatment with or without sonication.…”
Section: Discussionsupporting
confidence: 92%
“…Values of TPC and TAC of strawberries used for the treatments are in accordance for those already reported in strawberries from the same origin [19,41]. In the present study, TAC and TPC values did not overcome major changes after heat treatment with or without sonication.…”
Section: Discussionsupporting
confidence: 92%
“…However, there were no significant differences between them (P > 0.05). Therefore, results confirmed the effectiveness of the different washing treatments, since the WUVC and the combination treatment (WUVC+PA) are comparable to disinfection with free chlorine (P > 0.05), allowing the inhibition of the principal foodborne bacterial pathogens on fresh strawberries after the different decontamination methodologies tested during 2-min exposure (Nicolau-Lapeña et al, 2020;Ortiz-Solà et al, 2020).…”
Section: Foodborne Pathogenic Bacteria Inactivation On Strawberries A...supporting
confidence: 62%
“…For each sanitization treatment, 20 strawberries (25-g each, approximately) were used. Samples were washed for 2 min using the WUVC equipment in combination with 40-mg/L (ppm) peracetic acid (PA) (WUVC+PA), since previous work reported that this combination significantly reduced pathogenic microorganisms on strawberries (Nicolau-Lapeña et al, 2020). Moreover, WUVC alone and 200 ppm of sodium hypochlorite (NaClO) (pH 6.5) were also added as control treatments in the same equipment commented above.…”
Section: Sanitizing Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultraviolet radiation is a common sanitization method in medical settings and the heating, ventilation and air conditioning (HVAC) industry (Masse et al, 2018; Yang et al, 2018). It also has been effectively employed in water treatment application (Dotson et al, 2012; Li et al, 2017; Li et al, 2019), as well as food production activities (Garvey & Rowan, 2019; Nicolau‐Lapeña et al, 2020). Importantly, UV‐C radiation units designed to treat entire rooms are already commercially available.…”
Section: Introductionmentioning
confidence: 99%